FAKTOR-FAKTOR YANG MEMPENGARUHI PERANAN KEPEMIMPINAN KETUA KUB DALAM MEMBERDAYAKAN NELAYAN DI KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Sifa Urrahma; Fitri Eriyanti (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This article aims to analyze the factors that affect the role of leadership KUB's leader (KUB) in fisherman empowerment in IV Jurai sub-district Pesisir Selatan district. This research categorize 3 of KUB according to Pesisir Selatan fishery service category. The data were collected by observation, interview, and documentation. The informants of this research are fishery instructor, leader and members of KUB. The results indicate that there are several factors affect the Role of leadership KUB's leader in fisherman empowerment in IV Jurai sub-district Pesisir Selatan district. Among them are (1) Transparancy and Accountanbility of KUB's leader, (2) the ability of leader to motivate, (3) the concern of leader to members welfare, (4) leader's social position in society, (5) leader's experience and skill, (6) commitment of leader and members of KUB, (7) and resources in group.